PALEOPROTEOMICS STUDIES OF ANCIENT CAPRINAE: A REVIEW (Experimental biology, 2021)
In the Neolithic era, people began to graze sheep and goats primarily due to easier access to meat, milk, and fleeces. Thus, in ancient times, Caprinae were the key animals in the development of early domestication and agriculture. The analysis of ancient proteins of Caprinae from paleontological and archeological materials reveals new data on their migration, complements research on the diet of ancient people, their culture, and habits. Here, we discuss paleoproteomics methods, such as matrix-assisted laser desorption/ionization with time-of-flight mass analyzer (MALDI-TOF MS) and liquid chromatography with tandem mass spectrometry (LC-MS / MS). We will also consider the most important discoveries in the field of the study of ancient sheep and in which direction the paleoproteomics of Caprinae will develop in the near future.  In addition, general recommendations for analyzing data from ancient proteins are considered, for example, programs and requirements for databases. We will consider the main search algorithms in proteomics, as well as identify effective ones for identifying peptides and proteins. It also describes the commonly used ancient protein targets, and the basic principles of working with ancient samples. In addition, this review describes the main research conducted on ancient Caprinae of ancient proteins such as collagen, keratin, and milk proteins.